Oxygen Consumption Rate of Polychaeta Nereis sp. Different Sizes and Type of Feed - Eko Setio Wibowo; Endah Sri Palupi; I G A Ayu Ratna Puspitasari; Atang Atang (Marine Science Department Diponegoro University, 2019)
Nereis sp. contains amino acids and unsaturated fatty acids that can improve the quality of gamete stem cells and the quality of the resulting larvae. Nereis sp. can increase gamete cell maturation in the parent shrimp up to 70%. This triggers the exploitation these worms excessively in nature since there are no cultivation efforts to meet their needs. This condition encourages research on the biological aspects of Nereis sp. to complement the information that can support the cultivation of the worms. This research was conducted on Nereis sp. from the Jeruklegi Cilacap area with different types of feed. This study aims to determine the metabolic rate of the worms Nereis sp. at different sizes by giving different types of feed. This research use immature Nereis sp. which was maintained at 15 ppt salinity with three different body weight (0.3-0.6 g; 1.1-1.3 g and 1.8-2.04 g) with three different types of feed (D0 feed, feed flour of Spirulina sp. and ornamental fish feed tetra blitsz). The study was conducted experimentally with a randomized block design (RBD) method with six replications. The results showed the rate of oxygen consumption of Nereis sp. influenced by the size and type of feed given (P<0.05). Nereis sp. with size of 0.3-0.6 gr indicates the highest metabolic rate. Nereis sp. fed with flour of Spirulina sp. shows the highest metabolic rate. Appropriate feed to support the growth of Nereis sp. is D0 and tetra blits (low fiber feed).